Skilled Movements in Mice Require Inhibition of Corticospinal Axon Collateral Formation in the Spinal Cord by Semaphorin Signaling - Gu, Zirong (J Neurosci, 2019)
Corticospinal (CS) neurons in layer V of the sensorimotor cortex are essential for voluntary motor control. Those neurons project axons to specific segments along the rostro-caudal axis of the spinal cord, and reach their spinal targets by sending collateral branches interstitially along axon bundles. Currently, little is known how CS axon collaterals are formed in the proper spinal cord regions. Here, we show that the semaphorin3A (Sema3A)–neuropilin-1 (Npn-1) signaling pathway is an essential negative regulator of CS axon collateral formation in the spinal cord from mice of either sex. Sema3A is expressed in the ventral spinal cord, whereas CS neurons express Npn-1, suggesting that Sema3A might prevent CS axons from entering the ventral spinal cord. Indeed, the ectopic expression of Sema3A in the spinal cord in vivo inhibits CS axon collateral formation, whereas Sema3A or Npn-1 mutant mice have ectopic CS axon collateral formation within the ventral spinal cord compared with littermate controls. Finally, Npn-1 mutant mice exhibit impaired skilled movements, likely because of aberrantly formed CS connections in the ventral spinal cord. These genetic findings reveal that Sema3A–Npn-1 signaling-mediated inhibition of CS axon collateral formation is critical for proper CS circuit formation and the ability to perform skilled motor behaviors. SIGNIFICANCE STATEMENT CS neurons project axons to the spinal cord to control skilled movements in mammals. Previous studies revealed some of the molecular mechanisms underlying different phases of CS circuit development such as initial axon guidance in the brain, and midline crossing in the brainstem and spinal cord. However, the molecular mechanisms underlying CS axon collateral formation in the spinal gray matter has remained obscure. In this study, using in vivo gain-of- and loss-of-function experiments, we show that Sema3A–Npn-1 signaling functions to inhibit CS axon collateral formation in the ventral spinal cord, allowing for the development of proper skilled movements in mice.